Morality of COVID-19 Global Pandemic - CB. Kusmaryanto (P3TK, Sanata Dharma University, 2021)
The unprecedented global pandemic of COVID-19 creates many problems. No country in the world is ready to deal with this pandemic and some of them do not know how to overcome this pandemic. The victims of this pandemic (human and non-human) is very big and soaring every day. There are millions of infected and thousands of deaths around the world. At the same time, there are no available effective vaccines. The only available vaccine is for emergency used that we don’t know yet exactly the efficacy and the side effects of it. This situation creates many moral and ethical problems. We try to resolve some moral problems in the light of magisterial teachings to know how to answer some moral problems related to global COVID-19 pandemic.